NutritionTherapy in ICU Patiens - Kestriani, Nurita Dian; Budipratama, Dhany; Pradian, Erwin (Majalah Anestesia dan Critical Care, 2015)
Under ordinary circumstances, feeding is not considered as medical therapy. When normal diet fail to meet daily requirements or when assessment documents deficiencies, then nutritional planning becomes a part of medical therapeutics. The goals of nutritional support for critically ill patients include preserving tissue mass, decreasing usage of endogenous nutrient stores and catabolism, and maintaining or improving organ function (i.e., immune, renal, and hepatic systems; muscle). Specific goals include improving wound healing, decreasing infection, maintaining the gut barrier (decreasing translocation), and decreasing morbidity and mortality all of which may contribute to decreasing the ICU or hospital stay and hospitalization costs.